Developing wine tourism experiences. A discrete choice analysis using best-worst scaling data - Giacomo Del Chiappa; Juan Carlos Martin; Concepción Román (Wine Economics and Policy, 2022)
The aim of this research is to aid winery managers in bundling a plethora of different service features to meet the wine tourists’ expectations. A discrete choice model using best-worst scaling (BWS) data is estimated to obtain the relative importance of the attributes included in the analysis. Findings show that the most important aspects that make wineries attractive are: to offer wine tastings and “tour & visits”, to provide visitors with wine specialists/tour guides and, finally, to make the surrounding area and natural environment as pleasant as possible. Furthermore, the study highlights that wine tourists’ preferences are heterogeneous.